Finding God in the dark : faith, disappointment, and the struggle to believe - Kluck, Ted.; Martin, Ronnie (Minneapolis, Minn. : Bethany House, 2013)
"Popular author and award-winning musician help readers who struggle with doubt because of personal loss and disappointments"--Provided by publisher.
Includes bibliographical references.
Includes bibliographical references.
Keywords: Faith; Disappointment -- Religious aspects -- Christianity; Loss (Psychology) -- Religious aspects -- Christianity